Ambivalenzen pädagogischen Handelns Reflexionen der Betreuung von Menschen mit ›geistiger Behinderung‹ - Trescher, Hendrik (Gesellschaft der Unterschiede, 2018)
This book analyses and discusses the complexity of pedagogical action in the context of inpatient assistance for the disabled in a variety of ways - both theoretically and practically.